Mechanical strength of photonic crystal fibres - Matusewicz, Michał Artur; Wójcik, Jan; Mergo, Paweł; Walewski, Aleksander (Photonics Letters of Poland, 2010)
Most of the glass fractures start from flaws on the glass surface. The outer surface of optical fibres is protected from the influence of mechanical and chemical factors by a thin layer of polymer protective coating. Photonic crystal fibres have, besides outer glass surface, inner glass surface of even an order of magnitude greater area. This inner surface is not exposed to mechanical factors. However, it is not protected from chemical agents, most importantly ? water vapour. The hypothesis of relatively lower mechanical reliability of photonic crystal fibres in comparison to classical optical fibres was initially confirmed in our previous works. We present the work containing a quantitative mechanical strength description of two kinds of optical fibre mentioned above.